Vascular Endothelial Growth Factor Receptors in the Vascularization of Pancreatic Tumors: Implications for Prognosis and Therapy - Craig Grobbelaar; Vanessa Steenkamp; Peace Mabeta (Current Issues in Molecular Biology)
In pancreatic cancer (PC), vascular endothelial growth factor (VEGF) and its primary receptor, vascular endothelial growth factor receptor (VEGFR)-2, are central drivers of angiogenesis and metastasis, with their overexpression strongly associated with poor prognosis. In some PC patients, VEGF levels correlate with disease stage, tumor burden, and survival outcomes. However, therapies targeting VEGF and VEGFR-2, including tyrosine kinase inhibitors (TKIs) and monoclonal antibodies, have demonstrated limited efficacy, partly due to the emergence of resistance mechanisms. Resistance appears to stem from the activation of alternative vascularization pathways. This review explores the multifaceted roles of VEGFRs in pancreatic cancer, including VEGFR-1 and VEGFR-3. Potential strategies to improve VEGFR-targeting therapies, such as combination treatments, the development of more selective inhibitors, and the use of biomarkers, are discussed as promising approaches to enhance treatment efficacy and outcomes.